Elaboracão de pão sem glúten adicionado de farinhas de batata yacon, batata doce e batata cará - Almeida, Elenisse Alberton de (2015)
Bread is one of the most popular staple food in the world with its nutritional value, low price and simplicity of use, it is of civilizations diets base. Celiac disease (CD) is a permanent intolerance to gluten, characterized by the total or subtotal atrophy of the mucosa of the proximal small intestine and consequent malabsorption of food in genetically susceptible individuals. Whereas is growing every day the number of celiac people, and with this demand there is a need to develop new products, this study aimed to the development of gluten-free bread added yacon potato flour, sweet potato and yam potato. It was used experimental design of mixtures simplex centroid. Analyzed - if the physico-chemical properties (protein, lipid and ash contents) and the dough rheological properties (strength and specific volume) from seven formulations. It was observed that the mixture of pure sweet potato flour and ternary mixture showed softer and more specific volume of breads. A binary mixture of yacon potato flour, sweet potato flour showed the highest protein content, while the ternary mixture, met the highest content of lipids and the pure blends the lowest ash content. Results of these analyzes showed that it is possible to produce breads with the addition of flour, which were in pure formulations or mixtures, for the elaborate product displays characteristics suitable for baking.